Bahasa Inggris - Abdillah Sani, Ilham; Lapatta, Nouval Trezandy; Ngemba, Hajra Rasmita; Fahlevi, Mohammad Fazrin (AI Society & STMIK Indonesia, 2024)
Implementing a digital-based hazardous work licensing management system at PT Citra Palu Minerals is intended to enhance the efficiency and transparency of the work permit process. The research methodology involves a qualitative approach, Agile methodology system development, and integration with WhatsApp for notifications. The research findings indicate that this system simplifies the submission, approval, and monitoring of work permits in a structured manner, thereby reducing the risk of work accidents. Black box testing demonstrates that the system's performance meets expectations, while the questionnaire results indicate a high level of user satisfaction with an average score of 4.3 out of 5. Implementing this system can serve as a model for enhancing occupational safety and health management in similar industries.